Ответ:
Пошаговое объяснение:
1 y'=4x³-6x²+1
3 f'(x)=
5 f'(x)=6x²+6x-4
7 f'(x)=x-cosx
9 f'(x)=
11 f'(x)= -3sinx-2x
13 f'(x)=
15 f'(x)=
17 f'(x)=12x³-12x²-24x
19 f'(x)= -9x²+4x-1
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
Пошаговое объяснение:
1 y'=4x³-6x²+1
3 f'(x)=![\frac{1}{2\sqrt{x} } -32x \frac{1}{2\sqrt{x} } -32x](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B2%5Csqrt%7Bx%7D%20%7D%20-32x)
5 f'(x)=6x²+6x-4
7 f'(x)=x-cosx
9 f'(x)=![2x-\frac{8}{x} -6 2x-\frac{8}{x} -6](https://tex.z-dn.net/?f=2x-%5Cfrac%7B8%7D%7Bx%7D%20-6)
11 f'(x)= -3sinx-2x
13 f'(x)=![2x+\frac{1}{cos^{2}x } 2x+\frac{1}{cos^{2}x }](https://tex.z-dn.net/?f=2x%2B%5Cfrac%7B1%7D%7Bcos%5E%7B2%7Dx%20%7D)
15 f'(x)=![3x^{2} +\frac{1}{sin^{2}x } 3x^{2} +\frac{1}{sin^{2}x }](https://tex.z-dn.net/?f=3x%5E%7B2%7D%20%2B%5Cfrac%7B1%7D%7Bsin%5E%7B2%7Dx%20%7D)
17 f'(x)=12x³-12x²-24x
19 f'(x)= -9x²+4x-1